The life of Russian business : (re)cognizing, (re)activating and (re)configuring institutions - Casas i Klett, Tomas; Ponomareva, Yuliya (Emerald Publishing Limited : Information Age Publishing Inc., 2018)
The mainstream perception of Russian business today is framed by images of wild capitalism and a Dutch-diseased resource-dependent economy with poorly functioning rules and institutions. Despite the continued relevance of these issues in the current environment, readers of this book will discover that business in Russia has undergone a remarkable transformation. Important characteristics of the contemporary Russian business climate include the rise of a new generation of Russian business leaders and entrepreneurs, a variety of innovative and adaptive business strategies developed to respond to the increasingly VUCA world, a confident middle class with significant purchasing power, as well as a surprising level of integration in the world economy, including increasingly with China and its Belt and Road Initiative (BRI). These evolving developments have received little attention from researchers and practitioners.This book has been written by Russian experts and thought leaders to address this knowledge gap. The five sections provide a diverse but integrated set of opinion pieces, analyses and cases about Russian business covering markets and macro perspectives, strategy and governance, innovation and entrepreneurship, internationalization and leadership. The aim is to overcome preconceptions by illustrating the underreported and multifaceted nature of the life of Russian business and take the reader closer to what is really happening on the ground. The book contains more than 50 contributions from 54 authors representing opinion leaders in Russia and abroad including prominent academics and businessmen.The Life of Russian Business is aimed at practitioners, policy-makers and educators, as well as those generally interested in Russia. By disseminating state-of-the-art insights on Russian decision-makers and institutions, the book ultimately delivers a well informed and balanced guide for those wishing to participate in Russia's economy.
Keywords: Business enterprises -- Russia (Federation); Russia (Federation) -- Commerce.; Russia (Federation) -- Economic conditions -- 21st century.; Business & Economics -- Commerce.; Business studies: general.; Microeconomics.; elektronické knihy; electronic books